T cell protein tyrosine phosphatase attenuates T cell signaling to maintain tolerance in mice - Wiede, Florian (American Society for Clinical Investigation, 2011)
Many autoimmune diseases exhibit familial aggregation, indicating that they have genetic determinants. Single nucleotide polymorphisms in PTPN2, which encodes T cell protein tyrosine phosphatase (TCPTP), have been linked with the development of several autoimmune diseases, including type 1 diabetes and Crohn’s disease. In this study, we have identified TCPTP as a key negative regulator of TCR signaling, which might explain the association of PTPN2 SNPs with autoimmune disease. We found that TCPTP dephosphorylates and inactivates Src family kinases to regulate T cell responses. Using T cell–specific TCPTP-deficient mice, we established that TCPTP attenuates T cell activation and proliferation in vitro and blunts antigen-induced responses in vivo. TCPTP deficiency lowered the in vivo threshold for TCR-dependent CD8(+) T cell proliferation. Consistent with this, T cell–specific TCPTP-deficient mice developed widespread inflammation and autoimmunity that was transferable to wild-type recipient mice by CD8(+) T cells alone. This autoimmunity was associated with increased serum levels of proinflammatory cytokines and anti-nuclear antibodies, T cell infiltrates in non-lymphoid tissues, and liver disease. These data indicate that TCPTP is a critical negative regulator of TCR signaling that sets the threshold for TCR-induced naive T cell responses to prevent autoimmune and inflammatory disorders arising.